Experimental Study on Mechanism of Graphene Oxide-Modified Coral Sand Cement Mortar to Resist Sulfate Erosion - Bin Chen; Jianlin Zhang; Yanlin Zhao; Yiwei Lu (Geofluids)
Coral sand particles with low strength and rich pores affect the mechanical properties and durability of their cement-based materials. This paper investigates the mechanical properties and internal pore evolution of graphene oxide-modified coral sand cement mortar under sulfate erosion environment, aiming to better understand the effect of graphene oxide on the mechanical properties of coral sand cement mortar under an erosion environment, especially in wet and dry cycles. Mechanical properties of coral sand cement mortar were tested with different amounts of graphene oxide and different erosion cycles to understand the relationship between the change of flexural and compressive strength and the content and erosion cycle. The microscopic parameters of hydration products and internal dissolution pores were analyzed by XRD and SEM. The results showed that the degree of erosion performance improvement is related to the content of GO, and the two are positively correlated at first and then negatively correlated. At 0.03 wt% content, the retardation effect is the best. There were more orderly pore arrangement with less morphological complexity, when the dissolution amount of Ca(OH)2, porosity, total pore area, pore number, probability entropy, average form factor, and fractal dimension decreased. Coral sand cement mortar increases resistance to sulfate attack, which graphene oxide inhibits the formation of new dissolution pores and the expansion of original pores.